Network of anxiety and depression symptoms in older Chinese adults living alone: a cross-sectional study - Chen, Wenqin; Zhao, Xin; Xu, Tao; Fang, Linghui; Hong, Chen; Xie, Yiqian; Yan, Weiman; Zhou, Xiaolu; He, Yang (Frontiers in Psychiatry, 2025)
BackgroundWith the rapid aging of China’s population, the proportion of older adults living alone has increased significantly, bringing their mental health concerns into sharp focus. This study aims to explore the network structure of anxiety and depressive symptoms among older Chinese adults who live alone, thereby identifying central and bridging symptoms to provide scientific evidence for potential intervention targets in prevention and treatment.MethodsA total of 1,952 older Chinese adults, aged 65 and older, living alone, were selected from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) conducted in 2017-2018. We assessed anxiety and depressive symptoms using Generalized Anxiety Disorder Scale (GAD-7) and the Center for Epidemiologic Studies Depression Scale (CES-D). We identified central and bridge symptoms via expected influences (EI) and bridge expected influences (BEI); network stability was evaluated using bootstrap methods.ResultsThe network structure uncovered four crucial connections between anxiety and depressive symptoms. GAD4 “Trouble relaxing”, GAD2 “Uncontrollable worry”, and CESD3 “Feeling blue/depressed” exhibited the highest EI values within the network. Meanwhile, GAD1 “Nervousness or anxiety” and CESD10 “Sleep disturbances” showed the highest BEI values within their respective communities.ConclusionThis exploratory study is the first to examine the reciprocal relationship between depressive and anxiety symptoms in older Chinese adults living alone. Targeting these central and bridging symptoms may effectively prevent comorbidity and facilitate targeted interventions for those at risk or currently experiencing these symptoms.